Measurement of the electric potential and the magnetic field in the shifted analysing plane of the KATRIN experiment - Aker, Max; Spanier, Felix (The European physical journal. C, Particles and fields, 2024)
The projected sensitivity of the effective electron neutrino-mass measurement with the KATRIN experiment is below 0.3 eV (90 % CL) after 5 years of data acquisition. The sensitivity is affected by the increased rate of the background electrons from KATRIN’s main spectrometer. A special shifted-analysing-plane (SAP) configuration was developed to reduce this background by a factor of two. The complex layout of electromagnetic fields in the SAP configuration requires a robust method of estimating these fields. We present in this paper a dedicated calibration measurement of the fields using conversion electrons of gaseous $$^83m$$Kr, which enables the neutrino-mass measurements in the SAP configuration.